An Optimum Design Sapphire-Fiber Bragg Grating for High-Temperature Sensing - Dedi Irawan; Khaikal Ramadhan; Azhar Azhar (Postgraduate, University of Mataram, 2022)
Fiber Bragg grating (FBG) sensors have limitations in measuring high and extreme temperatures because in general FBG sensors are made of silica fiber, which at high temperatures can interfere with the mechanical performance of the materials. In this paper, we propose an S-FBG (Sapphire Fiber Bragg Grating) sensor which is resistant to extreme environmental influences and high temperatures. By developing S-FBG to measure high temperatures, it is found that S-FBG has high sensitivity, every 10C change is obtained and the Bragg wavelength shifts as far as 30.24 nm, this result is greatly influenced by the thermo-optic coefficient, and the coefficient of expansion-thermal. The design also evaluates the Gaussian apodization profile to improve sensor accuracy in monitoring temperature.